2013
DOI: 10.2176/nmc.53.34
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Injection of Contrast Medium Inducing Dysfunction of the Blood-Brain Barrier

Abstract: An early 60s-year-old man suffered reversible dysfunction of the blood-brain barrier (BBB) induced by repeated injection of contrast medium during coil embolization of intracranial unruptured aneurysm. He presented with convulsion during coil embolization, and neurological symptoms of aphasia and right hemiparesis continued for 5 days, and then improved completely. All transient radiological abnormalities were limited to the territory of the left internal carotid artery, where contrast medium was injected repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In terms of contrast medium used, while some reports describe the case with low doses, 10) many suggest that event is associated with the injected dose of the contrast medium and the number of injections. 11 13) Uchiyama et al reported that blood-brain barrier dysfunction is affected by the injection of high concentrations, low temperatures and repeated injections with short interval into the same blood vessel. 13) In this study, the mean dose of contrast medium was approximately 250 ml (mean 220 ml in hemodialysis and 285 ml in non-hemodialysis patients).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of contrast medium used, while some reports describe the case with low doses, 10) many suggest that event is associated with the injected dose of the contrast medium and the number of injections. 11 13) Uchiyama et al reported that blood-brain barrier dysfunction is affected by the injection of high concentrations, low temperatures and repeated injections with short interval into the same blood vessel. 13) In this study, the mean dose of contrast medium was approximately 250 ml (mean 220 ml in hemodialysis and 285 ml in non-hemodialysis patients).…”
Section: Discussionmentioning
confidence: 99%
“…On follow-up CT, high-density areas disappear rapidly, often with resolution of symptoms. 18,19) In our patient, the head MRI findings resembled those of PRES, but the condition could be differentiated from PRES because the lesion was located in the unilateral frontotemporal region, high-intensity signals were detected on DWI, and abnormal signals did not disappear on follow-up MRI. Herpes encephalitis could also be differentiated from contrast-induced encephalitis because it occurred 30 days after endovascular treatment, and no high-density area was noted on head CT.…”
Section: Disclosure Statementmentioning
confidence: 55%
“…18,19) PRES is supposed to be caused by vascular edema primarily in the posterior circulation due to disruption of the blood-brain barrier. It is characterized by symptoms including headache, altered consciousness, convulsion, and cortical blindness.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Mechanisms such as disruption of the blood-brain barrier (BBB) caused by reperfusion and influx of a highconcentration contrast medium, and stagnation of the contrast medium due to insufficient recanalization of the capillaries despite recanalization of the major artery ("noreflow phenomenon") have been proposed. 13) Iwata et al 26) reported patients who developed HA after coil embolization for unruptured cerebral aneurysms and speculated that they were caused by disruption of the BBB by the contrast medium.…”
Section: Discussionmentioning
confidence: 99%